Submarine cave sponges of the genus Rhabderemia (Demospongiae, Biemnida, Rhabderemiidae) from the Ryukyu Islands, southwestern Japan: rediscovery of R. forcipula and description of a new species - Ise, Yuji; Tajiri, Rie; Mizuyama, Masaru; Fujita, Yoshihisa (Zootaxa, 2025)
Two species of Rhabderemia, R. ginamaensis sp. nov. and R. forcipula (Lévi & Lévi, 1989), are reported from submarine anchialine caves of the Ryukyu Islands, Japan. Rhabderemia ginamaensis sp. nov., collected from the submarine cave of Ginama, Okinawa Island, differs from other congeners by its thinly encrusting morphology and the presence of microxea. Rhabderemia forcipula (Lévi & Lévi, 1989), once collected from the mesophotic zone of the Philippine Sea, was rediscovered for the first time since its original description in the dark nearshore submarine cave of Shimoji Island, Miyako Island Group. The species is characterized by a plumo-reticulate skeleton and spiculation: rhabdostyles, rugose microstyles, and sigmoid microscleres in two size classes, the larger ones being spirosigma and thraustosigma. A redescription of the type specimen and a detailed description of the newly collected specimens are provided to understand the morphological variation of the spicules, and to confirm the conspecificity of the type specimen and the submarine cave specimens. The two species, R. ginamaensis sp. nov. and R. forcipula are a new record of Rhabderemia and the family Rhabderemiidae from Japan, and the first report of Rhabderemia from submarine anchialine caves in the Indo-West Pacific. In addition, R. forcipula is the first species of the genus to be found from both a submarine cave and a mesophotic zone in the Indo-West Pacific.